Pendidik Dalam Perspektif Islam - Mohamad Samsudin (Al Ashriyyah, 2019)
The purpose of this study is first: to analyze the verses of the Qur'an and the hadith of the Prophet about the existence of educators; second, to find out how the Rasulullah saw. has been implementing his role as an ideal educator in delivering his treatise. To achieve this goal, the author uses research that is library research using written materials, both the Koran, Hadith and other scientific books. This research uses the maudlū'i interpretation method approach. This is done considering that this research is related to a concept in Islam, so the author analyzes the concept based on valid nasal arguments, namely the verses of the Koran and authentic hadiths. Then these verses and hadiths are interpreted based on the opinion of the mufasir and muhaddits by connecting the diverse problems in the argument between one another so that all problems can be interrelated with one another like one problem. The results showed that there are many Qur'anic verses that explain the role and function of educators in various terms. The term variability has different meanings. The different terms and meanings are all played by Rasulullah saw. as a plenary educator figure in presenting his treatise to friends